Third-generation holocaust representation : trauma, history, and memory - Aarons, Victoria 1952- (Cultural expressions of world war II, 2017)
Victoria Aarons and Alan L. Berger show that Holocaust literary representation has continued to flourish—gaining increased momentum even as its perspective shifts, as a third generation adds its voice to the chorus of post-Holocaust writers. In negotiating the complex thematic imperatives and narrative conceits of the literature of these writers, this bold new work examines those structures, ironies, disjunctions, and tensions that produce a literature lamenting loss for a generation removed spatially and temporally from the extended trauma of the Holocaust. Aarons and Berger address evolving notions of “postmemory”; the intergenerational transmission of trauma; inherited memory; the psychological tensions of post-Holocaust Jewish identity; tropes of memory and the personalized narrative voice; generational dislocation and anxiety; the recurrent antagonisms of assimilation and alienation; the imaginative reconstruction of the past; and the future of Holocaust memory and representation